The relationship between hospital ethical climate and continuing education in nursing ethics. - Ayaka Okumoto; Satoko Yoneyama; Chiharu Miyata; Ayae Kinoshita (PLoS ONE, 2022)
Background In recent years, there has been a growing interest in the importance of creating a healthy ethical climate. Although relationship with various factors and the ethical climate have been reported, understanding of the relationship between ethical education and ethical climate is limited. Aim This study aims to investigate the relationship between ethical climate, personal characteristics, and continuing education for ethics. Methods This study conducted a quantitative cross-sectional survey of 605 nurses in 3 teaching hospitals in Japan. Multiple-regression analysis was used to assess the relationship between ethical climate and demographic characteristics and continuing education. Further mean of ethical climate scores were compared between received continuing education and did not, using analysis of covariance adjusted for demographic variables. Findings The ethical climate showed significant association with hospital, gender, specialty of the unit, experience of ethics education, in-service ethical training, and workshops/ academic conferences on nursing ethics. In multiple-regression analysis, attending in-service ethical training increased the mean of ethical climate score (p = 0.031) and workshops/ academic conferences decreased the mean score (p = 0.028). Adjusted-mean of ethical climate score of nurses who had in-service training was significantly higher than those who had not (p = 0.038), whereas adjusted-mean of it of nurses who had attended workshops/ academic conferences was significant lower (p = 0.033). Discussion In-service training on ethics was associated with the positive ethical climate. Hospital should enhance ethical education. Conclusion Ethical climate related to the nurses' personal characteristics and continuing education. We propose that organizational support for ethical education may be effective in raising the ethical climate of the workplace.